APPLICATION OF ISLAMIC BUSINESS ETHICS TO PROMOTION AND SERVICE STRATEGIES AT MS GLOW BRONI JAMBI - Rohadil Ilham; Maulana Yusuf; Angger Hidayat (Universitas Islam Darul 'ulum Lamongan, 2025)
Islamic business ethics is a principle that distinguishes between good and bad and right and wrong that must be applied in transactions, behavior and relationships with business partners that originate from Islamic teachings, namely the Al-Qur'an and Hadith. This research aims to determine the application of Islamic business ethics to promotional and service strategies at Ms Glow Broni, Jambi City using the principles of Islamic business ethics. The method used in this research is descriptive qualitative, data collection in this research uses observation, interviews and documentation methods. The research results show that the application of Islamic business ethics in promotional and service strategies at Ms Glow Broni Jambi is good and has been implemented in her business. The obstacles experienced by the Ms Glow broni Jambi Agent in applying the principles of Islamic business ethics in promotional and service strategies are the lack of available workforce and the lack of thoroughness of Ms Glow employees in conveying information to consumers which makes consumers feel disadvantaged.